Konvergensi Jurnalistik Melalui Penggunaan OSINT Pada Proses Produksi Berita di Narasi TV - Sihaloho, Kiki Evelin Olivia; Nurcahyo, Moch. Subechi (DIGICOM : Jurnal Komunikasi dan Media, 2024)
This research aims to find out how journalistic convergence occurs through the use of OSINT in the news production process at Narasi TV. This research uses the theories of investigative journalism and journalistic convergence. Investigative journalism theory explains journalistic practices that uncover the truth in an important case. Journalistic convergence theory explains how journalists work multitasking. The researcher also used Robert K. Yin's case study research method which is based on the main questions about 'Why, and 'How' OSINT can be used in Narasi TV investigative journalism practice. The research results found that Narasi TV carried out digital investigations using OSINT and carried out newsgathering convergence. In the process of verifying and accuracy of data obtained through the OSINT method, Narasi TV carries out verification directly in the field so that the data obtained is valid.